Brainwashed for war, programmed to kill - Chang, Matthias (Thinker's Library, 2005)
In a continuing effort by the best-selling author of Future Fastforward, the erudite scholar of political intrigue and conspiracy, Matthias Chang, sets for the modi operandi of the Zionist masterminds to brainwash and program the minds of the people to achieve their goal of world domination. Tracing back four decades and more, Brainwashed for War - Programmed to Kill documents the atrocities carried out by the imperialist forces to subjugate the peoples of the world. Replete with documentary evidence, this volume exposes the vile propaganda warfare, mind-control, and brainwashing operations carried out by some of the most powerful clandestine intelligence agencies in the word - including Mossad, the CIA and MI6 - and how these operations have come to impact our lives today. Included in this opus of veritable knowledge for our future true independence and freedom are 14 appendices containing historical speeches and literature, declassified top secret documents, and intelligence doctrines - of which all but three are reproduced in full - amounting to just about 200 pages of arduously researched must-read information!